Evaluación de la calidad de agua de los pozos sector porvenir la caña, distrito de virú y su ulterior potabilización - Narváez Gonzales, Wilson Roberto (2022)
Our country still has a deficit in sanitation, at present there is a population that is approximately 10% that does not have drinking water. In public health, water quality is a very important element since it is linked to diseases that affect health; we see ourselves as convenient to carry out this research work. The objective of this research work is to evaluate the water quality of wells in the Porvenir La Caña district of Virú during the months of October, November, December 2020 and January 2021 to determine if these waters are suitable for human consumption of according to current regulations and if not, provide an alternative for purification. The results obtained show that the waters of the wells in the study sector present on average total coliforms in a range of 87 - 1175 NMP / 100ml and thermotolerant in a range of 2.7 - 16.1 NMP / 100ml; exceeding the maximum permissible limits by the Regulation of the Quality of Water for human consumption (DS 031-2010-SA), according to its annex 1. Reason for which an economic alternative is given in this work to make it suitable and comply with the regulations current.